Konsumsi Makronutrien pada Ibu Hamil Kekurangan Energi Kronik (KEK) di Masa Pandemi Covid-19 - Ellyani Abadi; Linda Ayu Rizka Putri (Jurnal Kesehatan Manarang, 2020)
Chronic Energy Deficiency (CED) is one of the nutritional problems which prevalence in Southeast Sulawesi is 21.9%, Kendari City is 14.37%, and Puuwatu Public Health Center is 11.04% (the national target for CED is 5%). The direct cause of CED is low intake of macronutrients such as energy, protein, fat and carbohydrates. During the Covid-19 pandemic, everyone is advised to stay at home so that access to food is very limited and causes a lack of nutritional intake for pregnant women. The study aimed to determine the macronutrient consumption of pregnant women who suffer from CED during the Covid-19 Pandemic. The research was conducted descriptively with a survey design. This research was conducted in June – September 2020 in the Puuwatu Public Health Center, Kendari City, Southeast Sulawesi. The research sample was 35 pregnant women in the 3rd trimester who had CED and were taken using saturated samples. Data collection by interview using a form 2x24 hour recall and also anthropometric measurements using microtoice and weight scales. Data were analyzed descriptively and presented in tabular and narrative form. The results showed that the energy and carbohydrate intake of pregnant women was 100% in the category of severe deficit, 91.4% heavy deficit protein intake and 8.6% mild deficit, then fat intake 57.1% severe deficit, 20% mild deficit and 8,6% mild deficit. In conclusion, the intake macronutrient of pregnant women in CED during the Covid-19 pandemic is mostly a severe deficit.